High Risk HPV E6/E7 Oncoprotein Expression in Women with High Grade Squamous Intraepithelial Lesion - Valença, Jefferson Elias Cordeiro; Gonçalves, Ana Katherine; Guerreiro da Silva, Ismael Dale Cotrim; Eleutério Junior, José; Tenório da Silva, Terezinha; Bruneska, Danyelly; Ximenes, Ricardo Arraes de Alencar (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Purpose To correlate the expression of high-risk HPV E6 mRNA with pap smear, colposcopy, and biopsy results in women with high grade squamous intraepithelial lesion (HSIL).Methods A cross-sectional study was performed on women referred for primary care services after cytological diagnosis of HSIL. We evaluated the expression of E6/E7 mRNA of HPV types 16,18,31,33, and 45 and correlated the results with those of Pap smear, colposcopy, and biopsy. For amplification/detection of mRNA E6 / E7 we used NucliSENSEasyQ kit to detect HPV mRNA by polymerase chain reaction with primers/probes for HPV types 16, 18, 31, 33, and 45.Results Out of 128 valid tests, the results of 30 (23.4%) tests were negative and 98 (70%) tests were positive. Only one type of HPV was detected in 87.7% of the E6/E7 mRNA positive cases. HPV16 was detected in 61.2% of the cases, followed by HPV33 (26.5%), HPV31 (17.3%), HPV18 (10%), and HPV45 (4.08%). Pap smear tests revealed that the E6/E7 test was positive in 107 (83.8%) women with atypical squamous cells – high grade (ASC-H), HSIL, or higher. The E6/E7 test was positive in 69 (57.5%) specimens presenting negative cytology results. When analyzing the association with colposcopy results, the frequency of positive E6/E7 results increased with the severity of the injury, ranging from 57.1% in women without colposcopy-detected injury to 86.5% in those with higher levels of colposcopy findings. Of the 111 women who underwent biopsy and E6/E7 testing, the E6/E7 test was positive in 84.7% of the women who presented with lesions of cervical intraepithelial neoplasia (CIN) grade 2 or higher. Finally, 41.2% of women with a negative biopsy presented a positive E6/E7 test.Conclusions E6/E7 mRNA expression was higher in women with HSIL and CIN grade 2 or higher.
Keywords: colposcopy; HPV; mRNA; Pap smear; women